2006
DOI: 10.1042/bst0340179
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitrogen oxides in the metabolism of ammonia-oxidizing bacteria

Abstract: Ammonia-oxidizing bacteria (AOB) can use oxygen and nitrite as electron acceptors. Nitrite reduction by Nitrosomonas is observed under three conditions: (i) hydrogen-dependent denitrification, (ii) anoxic ammonia oxidation with nitrogen dioxide (NO(2)) and (iii) NO(x)-induced aerobic ammonia oxidation. NO(x) molecules play an important role in the conversion of ammonia and nitrite by AOB. Absence of nitric oxide (NO), which is generally detectable during ammonia oxidation, severely impairs ammonia oxidation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…However, the proportion of NH 3 -N that accumulates as NO-N remains unknown in this study. Previous work showed that NH 3 -N can be directed to NO production, especially during IC limitation, which further supports our hypothesis (6,(40)(41)(42). Our gene expression data are in contrast with those in the previous study by Jiang et al (6), who showed increased expression of rh50, amo, and hao by qPCR, but these differences may be reflections of a different medium and different growth conditions in their study (6).…”
Section: Nitrosomonas Europaea Physiology Under Limiting Carboncontrasting
confidence: 57%
“…However, the proportion of NH 3 -N that accumulates as NO-N remains unknown in this study. Previous work showed that NH 3 -N can be directed to NO production, especially during IC limitation, which further supports our hypothesis (6,(40)(41)(42). Our gene expression data are in contrast with those in the previous study by Jiang et al (6), who showed increased expression of rh50, amo, and hao by qPCR, but these differences may be reflections of a different medium and different growth conditions in their study (6).…”
Section: Nitrosomonas Europaea Physiology Under Limiting Carboncontrasting
confidence: 57%
“…It is known that a large quantity of nitrous oxide (N 2 O) can be emitted during the process of biological denitrification if organic carbon is limited or during nitrification when oxygen is limited (Itokawa et al 2001;Kampschreur et al 2006). Recent studies showed that natural and artificial wetlands could be important emission sources of N 2 O (Wang et al 2006b;Søvik et al 2006).…”
Section: Potential Relationship To Nitrous Oxide (N 2 O) Emissionsmentioning
confidence: 99%
“…Classically, ammonia oxidizers are known to use oxygen (i) for the oxidation of NH 3 to hydroxylamine (NH 2 OH) and (ii) as terminal electron acceptor in their electron transport chain. For oxidizing NH 3 , dinitrogen tetroxide (N 2 O 4 ), rather than O 2 , has been proposed to be the primary oxidant, as described in the NO x cycle hypothesis (Schmidt et al, 2001;Kampschreur et al, 2006;Schmidt, 2008) in which NO is an important intermediate: NO produced by NO 2 À reduction can feed into the NO x cycle and the nitrite reductase is thereby indirectly involved in ammonia oxidation. This is supported by lower growth yield and growth defects (Schmidt et al, 2004) and slower ammonia oxidation rate (Cantera and Stein, 2007a) in Nitrosomonas europaea nirK mutants.…”
Section: Introductionmentioning
confidence: 99%